Global Spread of Human Chromoblastomycosis Is Driven by Recombinant Cladophialophora carrionii and Predominantly Clonal Fonsecaea Species. - Shuwen Deng; Clement K M Tsui; A H G Gerrits van den Ende; Liyue Yang; Mohammad Javad Najafzadeh; Hamid Badali; Ruoyu Li; Ferry Hagen; Jacques F Meis; Jiufeng Sun; Somayeh Dolatabadi; Bernard Papierok; et al. (Public Library of Science (PLoS), 2015)
Global distribution patterns of Cladophialophora carrionii, agent of human chromoblastomycosis in arid climates of Africa, Asia, Australia, Central-and South-America, were compared with similar data of the vicarious Fonsecaea spp., agents of the disease in tropical rain forests. Population diversities among 73 C. carrionii strains and 60 strains of three Fonsecaea species were analyzed for rDNA ITS, partial β-tubulin, and amplified fragment-length polymorphism (AFLP) fingerprints. Populations differed significantly between continents. Lowest haplotype diversity was found in South American populations, while African strains were the most diverse. Gene flow was noted between the African population and all other continents. The general pattern of Fonsecaea agents of chromoblastomycosis differed significantly from that of C. carrionii and revealed deeper divergence among three differentiated species with smaller numbers of haplotypes, indicating a longer evolutionary history.